Somatic expansion of premutation alleles and the role of the mismatch repair and base excision repair proteins on repeat expansion in a mouse model of the fragile X-related disorders - Lokanga, Rachel Adihe (Division of Medical Biochemistry, 2016)
The Fragile X-related disorders arise from an unusual mutation in the X-linked FMR1 gene. The mutation involves expansion, or an increase in the number of repeats, in a CGG•CCG repeat tract located in its 5' untranslated region. FMR1 alleles carrying 55-200 repeats are called Premutation (PM) alleles, and cause Fragile X associated tremor/ataxia syndrome (FXTAS) and Fragile X-associated primary ovarian insufficiency (FXPOI). FMR1 alleles having more than 200 repeats are referred to as full mutation (FM) alleles and cause Fragile X syndrome (FXS). These different alleles arise by intergenerational expansion of the repeat tract from smaller unstable alleles by a mechanism that is unknown. We have shown that in addition to germ line expansion, somatic expansion also occurs in a human cell line in vivo and in a FX PM mouse model. In the mouse model, we found that the extent of somatic instability is dependent on age, gender and tissue. Specifically, organs such as brain, liver and gonads are susceptible to expand more than heart and kidney and expansion is much more frequent in males than in females. No differences were found between male and female mice in the levels of the DNA repair proteins that had already been implicated in repeat expansion in model systems of other disorders thought to arise via a similar mechanism. Neither were there any differences between males and females in the amounts of proteins produced from X-linked DNA repair genes. We also showed that estrogen did not protect against expansion. However, we found that PM alleles expanded exclusively when they were located on the active X chromosome. Thus some of the differences between males and xii females in the level of somatic expansion might be due to the fact that females undergo X inactivation and thus have the PM allele on the inactive X chromosome in half (~50%) of their cells. It also indicates that transcription and/or an open chromatin configuration is required for expansion in the FX PM mouse.